Macrophages in vascular inflammation and atherosclerosis - Cochain, Clement; Zernecke, Alma (Pflügers Archiv: European Journal of Physiology, 2017)
Atherosclerosis is characterized by lipid accumulation and chronic inflammation of the arterial wall, and its main complications—myocardial infarction and ischemic stroke—together constitute the first cause of death worldwide. Accumulation of lipid-laden macrophage foam cells in the intima of inflamed arteries has long been recognized as a hallmark of atherosclerosis. However, in recent years, an unexpected complexity in the mechanisms of macrophage accumulation in lesions, in the protective and pathogenic functions performed by macrophages and how they are regulated has been uncovered. Here, we provide an overview of the latest developments regarding the various mechanisms of macrophage accumulation in lesion, the major functional features of lesion macrophages, and how the plaque microenvironment may affect macrophage phenotype. Finally, we discuss how best to apprehend the heterogeneous ontogeny and functionality of atherosclerotic plaque macrophages and argue that moving away from a rigid nomenclature of arbitrarily defined macrophage subsets would be beneficial for research in the field.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Atherosclerosis; Immune cells; Inflammation; Macrophages